2022
DOI: 10.3390/molecules27144409
|View full text |Cite
|
Sign up to set email alerts
|

A Synergistic Effect of Phthalimide-Substituted Sulfanyl Porphyrazines and Carbon Nanotubes to Improve the Electrocatalytic Detection of Hydrogen Peroxide

Abstract: A sulfanyl porphyrazine derivative with peripheral phthalimide moieties was metallated with cobalt(II) and iron(II) metal ions. The purity of the macrocycles was confirmed by HPLC, and subsequently, compounds were characterized using various analytical methods (ES-TOF, MALDI-TOF, UV–VIS, and NMR spectroscopy). To obtain hybrid electroactive electrode materials, novel porphyrazines were combined with multiwalled carbon nanotubes. The electrocatalytic effect derived from cobalt(II) and iron(II) cations was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…The coordination of metal ions with porphyrazine molecules can enhance the properties of porphyrazine and endow them with new functions [49,50,52]. For example, copper porphyrazine molecules can serve as effective oxidants and act as catalysts in organic synthesis reactions; cobalt porphyrazine molecules are an important artificial photosynthetic catalyst that can decompose water into hydrogen and oxygen [50,53,54]; and the electron transfer and oxygenation properties of manganese porphyrazine molecules make them a potential biomedical research tool [49,55,56]. Furthermore, research has revealed that Sn-doped phthalocyanines possess tunable geometric and electronic structures on surfaces in the presence of the Sn atom [57,58].…”
Section: Introductionmentioning
confidence: 99%
“…The coordination of metal ions with porphyrazine molecules can enhance the properties of porphyrazine and endow them with new functions [49,50,52]. For example, copper porphyrazine molecules can serve as effective oxidants and act as catalysts in organic synthesis reactions; cobalt porphyrazine molecules are an important artificial photosynthetic catalyst that can decompose water into hydrogen and oxygen [50,53,54]; and the electron transfer and oxygenation properties of manganese porphyrazine molecules make them a potential biomedical research tool [49,55,56]. Furthermore, research has revealed that Sn-doped phthalocyanines possess tunable geometric and electronic structures on surfaces in the presence of the Sn atom [57,58].…”
Section: Introductionmentioning
confidence: 99%